2015
DOI: 10.1021/ja5126287
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organic/Inorganic Band-Edge Modulation of p-Si(111) Photoelectrodes: Effects of R, Metal Oxide, and Pt on H2 Generation

Abstract: The efficient generation of dihydrogen on molecularly modified p-Si(111) has remained a challenge due to the low barrier heights observed on such surfaces. The band-edge and barrier height challenge is a primary obstruction to progress in the area of integration of molecular H2 electrocatalysts with silicon photoelectrodes. In this work, we demonstrate that an optimal combination of organic passivating agent and inorganic metal oxide leads to H2 evolution at photovoltages positive of RHE. Modulation of the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(102 citation statements)
references
References 27 publications
6
96
0
Order By: Relevance
“…Meanwhile, Pt deposition shifted the secondary electron cutoff energy higher to 16.69 eV. Consistent with the shallow escape depth of photoexcited electrons in UPS, the rank order of these shifts in secondary electron cutoff are in agreement with the literature regarding the relative work functions of pSi‐DMO (5.07 eV), TiO 2 (4.8–5.0 eV)„ and Pt (5.64 eV) . Therefore, simple equilibration between the semiconductor and metal does not explain the changes observed electrochemically.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Meanwhile, Pt deposition shifted the secondary electron cutoff energy higher to 16.69 eV. Consistent with the shallow escape depth of photoexcited electrons in UPS, the rank order of these shifts in secondary electron cutoff are in agreement with the literature regarding the relative work functions of pSi‐DMO (5.07 eV), TiO 2 (4.8–5.0 eV)„ and Pt (5.64 eV) . Therefore, simple equilibration between the semiconductor and metal does not explain the changes observed electrochemically.…”
Section: Resultssupporting
confidence: 88%
“…Electron and hole conduction through the TiO 2 conduction and defect bands, respectively, allows TiO 2 to be a versatile overlayer, used for both photocathodes and photoanodes . However, these modes of conduction also represent possible losses due to the permeability of the overlayer to both majority and minority carriers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 11,12,45,46 In this work, it was reported that the greatest extent of band bending occurred on the p-Si(111)|H electrodes as compared with other surface moieties ( Table 2). As shown in Fig.…”
Section: Her Catalytic Performancementioning
confidence: 68%
“…12 A boron doped, Cz grown p-Si(111) wafer (single-side-polished, 450 AE 25 mm thick, Virginia Semiconductor Inc.) with 1.4-9 U-cm resistivity was used for organic functionalization of the surface. 12 A boron doped, Cz grown p-Si(111) wafer (single-side-polished, 450 AE 25 mm thick, Virginia Semiconductor Inc.) with 1.4-9 U-cm resistivity was used for organic functionalization of the surface.…”
Section: Preparation Of Organic-modied P-si(111) Substratementioning
confidence: 99%